2022
DOI: 10.1038/s41541-022-00480-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-TRAP/SSP2 monoclonal antibodies can inhibit sporozoite infection and may enhance protection of anti-CSP monoclonal antibodies

Abstract: Vaccine-induced sterilizing protection from infection by Plasmodium parasites, the pathogens that cause malaria, will be essential in the fight against malaria as it would prevent both malaria-related disease and transmission. Stopping the relatively small number of parasites injected by the mosquito before they can migrate from the skin to the liver is an attractive means to this goal. Antibody-eliciting vaccines have been used to pursue this objective by targeting the major parasite surface protein present d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…When used in combination with PyCSP, PyTRAP co-immunizations consistently resulted in enhanced probability of sterile protection compared to PyCSP-alone immunizations. Taken together with our recent finding that anti-TRAP mAbs can increase chances of sterile protection afforded by anti-CSP mAbs in a humanized mouse system 22 , these data suggest that the use of recombinant TRAP in co-immunization strategies still holds promise and should be revisited.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…When used in combination with PyCSP, PyTRAP co-immunizations consistently resulted in enhanced probability of sterile protection compared to PyCSP-alone immunizations. Taken together with our recent finding that anti-TRAP mAbs can increase chances of sterile protection afforded by anti-CSP mAbs in a humanized mouse system 22 , these data suggest that the use of recombinant TRAP in co-immunization strategies still holds promise and should be revisited.…”
Section: Discussionmentioning
confidence: 60%
“…However, developing a CSP-only malaria vaccine with high efficacy and durability of protection has been hampered by various roadblocks; and identifying additional PE vaccine antigens to augment anti-sporozoite immunity may be a promising strategy to fortify CSP-based vaccines. In our recent work, we have shown that plasma from mice immunized with recombinant TRAP-an exemplar PE antigen-inhibited sporozoites, and that passively transferred monoclonal antibodies could enhance anti-CSPmediated protection from mosquito-bite challenge 22 . Others have shown that active immunization with TRAP-CSP fusion proteins had protective effects in a similar experiment using the Plasmodium berghei-infected mosquito-bite challenge, although the individual contributions of anti-TRAP and anti-CSP responses were not completely defined 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we showed that many components of the inner membrane complex could become exposed during the initial process of invasion and be accessible for recognition by antibodies (22). Recently, we demonstrated that passively transferred monoclonal antibodies (mAbs) raised against TRAP can enhance the protective effect of anti-CSP mAbs (23). In the present study we investigated whether active immunization with non-CSP sporozoite antigens could enhance the anti-CSP response-mediated protection using the rodent parasite model.…”
Section: Introductionmentioning
confidence: 99%